Presentation Form of Candei Music Group in Sendari Song in Muara Enim - Indah Rizky Heryana; Wadiyo Wadiyo; Udi Utomo (Universitas Negeri Semarang, 2023)
This research aims to analyze the changes in the performance of Rejung Music and interpret the changes in the sociology of Rejung Music. This research uses qualitative research methods with an interdisciplinary approach, namely ethnomusicology and sociology. The research design used is a case study with a research focus on the form of performance, sociocultural changes in Rejung Music. The data in this study are primary and secondary data obtained from observations, interviews and document studies. Data validation is carried out by triangualation techniques, data sources and theories. Data analysis techniques include; data collection, data reduction, data presentation and data verification. The results of this study show that the art of Rejung Music has experienced changes in socio-cultural behavior both in presentation including the form of presentation of Rejung Music has changed from the time of its creation until now. The form of presentation of Rejung Music that has undergone changes includes the following components, 1) Rejung music is no longer just sung in the yard or in love, rejung music has evolved into contemporary music with traditional wraps that are often held at major events. 2) Rejung music used to only use a single guitar and now uses modern music ensembles 3) The musical instruments used are not only single Guitars, but are already diverse. 4) not having to use traditional costumes (shirt of Kurung).